PHYSICOCHEMICAL AND MICROBIOLOGICAL CHARACTERISTICS OFBEEF MEATBALLS IN PALU CITY - Sukisman Abdul Halid; Abdul Rahim (Tadulako University, 2018)
The aim of the study is to evaluate the physicochemical and microbiological characteristics of beef meatball produced and circulated in Palu City. The study used a completely randomized design with 8 micro, small and medium enterprises (MSMEs) where sampling was repeated three times to obtain 24 research samples. Parameters of analysis included water, ash, protein, fat, borax, formalin and total microbial content. The results show that beef meatball circulating in Palu City had water content (66.56 - 72.99%), ash content (1.28 - 1.99%), protein content (8.93– 10.76%). ), fat content (1.16 - 5.84%) and total microbes (1.92–7.97 log cfu / g) and borax content and beef meatball formalin showed negative values.